Exploring the Pattern of Stroke in Young Adults: Clinical Presentations, Risk Factors, and Implications for Early Detection and Management - Shahid, Muhammad Irtza; Khalid, Moiz; Sultan, Umar; Zainullah,; Jamil, Hafsa; Zafar, Qasim (Indus Journal of Bioscience Research, 2025)
Background: Stroke in young adults is an increasingly recognized clinical and public health concern. Unlike older populations, young stroke patients often present with diverse risk profiles and atypical symptoms, necessitating a targeted approach to diagnosis and management. Objective: To explore the clinical presentations, associated risk factors, and stroke patterns among young adults aged 15 to 49 years, with a focus on implications for early detection and prevention. Methods: This descriptive cross-sectional study was conducted at Allied Hospital, Faisalabad, from December 2024 to April 2025. A total of 95 young adults with confirmed stroke were enrolled. Data on demographics, clinical features, stroke subtypes, and risk factors were collected through a structured proforma. Results: Of the 95 patients, 63 (66.3%) had ischemic stroke and 32 (33.7%) had hemorrhagic stroke. The mean age was 36.4 ± 8.2 years, and 61.1% were male. Hemiparesis was the most common presentation (72.6%), followed by headache (29.5%) and aphasia (23.2%). Hypertension (56.8%), smoking (45.3%), and dyslipidemia (22.1%) were the most frequent risk factors. Statistically significant associations were observed between stroke type and hypertension (p = 0.01), smoking (p = 0.04), and dyslipidemia (p = 0.03). Conclusion: It is concluded that ischemic stroke is more prevalent than hemorrhagic stroke among young adults. Hypertension, smoking, and dyslipidemia are major modifiable risk factors. Early recognition of stroke symptoms and aggressive risk factor control are essential to mitigate the rising burden of stroke in younger populations.